Performance dispersion for evidence-based classification of stationary throwers - Frossard, L. (Prosthetics and Orthotics International, 2012)
Background: There is a need for better understanding of the dispersion of classification-related variable to develop an evidence-based classification of athletes with a disability participating in stationary throwing events.